ANALISIS DAMPAK IMPLEMENTASI PSAK 73 TERHADAP STRUKTUR NERACA DAN KINERJA KEUANGAN: STUDI KOMPARASI PADA PERUSAHAAN SEKTOR RITEL DAN SEKTOR NON RITEL DI BEI PERIODE 2018–2023 - Mohammad Rizky Yahya; Mohammad Djufri Dapi; Nur Afni Karim; Irfan H. Wasilu; Fahmi Karim (LPSDI Bina Patria, 2025)
This study aims to analyze the impact of the implementation of Indonesian Financial Accounting Standards (PSAK) 73 on the balance sheet structure and financial performance of companies. PSAK 73, which became effective in 2020, introduced significant changes in lease accounting, particularly in the recognition of lease liabilities and right-of-use assets. This research adopts a quantitative approach using a Difference-in-Differences design and panel fixed effects regression method, comparing retail and non-retail companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. The results indicate that PSAK 73 significantly increased the debt-to-equity ratio (DER) and debt-to-asset ratio (DAR), especially in the retail sector, but did not significantly affect profitability ratios (ROA and ROE). These findings suggest that PSAK 73 has a structural impact on the balance sheet but does not directly influence earnings performance. The results are important for investors, creditors, and regulators in assessing financial reporting risks and transparency following the adoption of PSAK 73.